Assessment of heparanase and heparin-binding growth and angiogenesis factors in the uterine cavity fluid in women with impaired reproduction - Wirstlein, Przemysław; Mikołajczyk, Mateusz; Skrzypczak, Jana (Journal of Medical Science, 2014)
Introduction. Numerous reports lead to conclusion that either the absence or insufficient amounts of heparanase and heparin binding growth factors on the luminal surface of the epithelium in the endometrium may be associated with impaired reproduction. The aim of this study was to assess the suitability of the fluid from the uterus to predict reproductive disorders. Material and methods. The group consisted of 32 women with 2 or more consecutive unexplained miscarriages, and 33 idiopathic infertility patients; the control group comprised 22 women with normal reproductive potential. Concentration of the studied factors was assayed by ELISA in uterine fluid. Results. The uterine flushings from women with two or more consecutive miscarriages showed significantly lower concentrations of HPA1 (p < 0.001) compared to the control group and infertile patients. In contrast, we didn't observe statistically significant differences of concentration of HB-EGF, VEGF, FGF2 in the studied groups. Statistically significant correlations were obtained between the levels of HPA1 and growth factors in all groups p < 0.05. The ROC curve was used to test the diagnostic value of HPA1. With a cut-off point of 8.56 U/L for HPA1 levels, we achieved 58.6% sensitivity and 84.6% specificity in the detection of women with recurrent miscarriage compared to fertile controls and infertile women combined. The area under curve (AUC) value was 0.751. Conclusions. The procedure for determining the concentrations of HPA1, HB-EGF, VEGF, FGF2 by ELISA in fluids derived from the uterine cavity is insufficient to predict either success of reproduction or reproductive disorders.